Cocoa Butter Substitute from Tengkawang (Shorea stenoptera) - Abd Aziz, Suraini; Gozan, Misri; Darmawan, Muhammad Arif (Wiley-VCH, 2024)
Tengkawang ( Shorea stenoptera ) is a potential endemic plant of Kalimantan. However, its production process is currently still carried out traditionally. Tengkawang butter (TB) has the potential to be a Cocoa butter equivalent (CBE) because it has a fatty acid composition and melting point close to cocoa butter (CB). The fatty acid profile of the TB was dominated by palmitic acid (16–24%), stearic acid (40–47%), and oleic acid (31–33%). The melting point of TB is at the human mouth (body) temperature of 35–37 °C. Physical and chemical processing of tengkawang is carried out to obtain the quality of TB according to the standard butter material. This chapter also discusses the economic feasibility based on process simulation. The utilization of TB as a substitute for CB has drawn attention as a strategy to achieve cost-effective food material production and conservation of endemic plants in Kalimantan.